Molecular Typing of Pneumococci for Investigation of Linked Cases of Invasive Pneumococcal Disease - Pichon, Bruno (American Society for Microbiology (ASM), 2010)
In winter 2007-2008, an outbreak of pediatric pneumonia caused by serotype 5 pneumococci was identified in a northeast London suburb. Variable number of tandem repeat analyses clustered these pneumococci from the other serotype 5 pneumococci in the United Kingdom, highlighting the importance of this discriminative typing method in supporting epidemiological investigations.